“Per speciem venandi”. Livy on Tarentum having been “hunted” by Hannibal - Matusiak, Patrycja (City and War, 2021)
Ancient authors Polybios, Livy and Appianus described the conquest of Tarentum by trickery by Hannibal in 212 BCE during the Second Punic War. The trick was related to Philemenos, who, under the guise of hunting, let Hannibal and the Carthaginians, who supplied him with game, into the city. The Roman historian, more than the Greeks, draws attention to the effect of the last of the hunts, making the hunted great boar (Tarentum boar) a metaphor for the city itself and a prefiguration of Hannibal. This ruse fits both the ways of conquering cities during the war and the wide variety of Punic deceits